2018
DOI: 10.1007/s12010-018-2773-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression of miRNAs Targeting mTOR and S6K1 Genes of mTOR Signaling Pathway Including miR-96, miR-557, and miR-3182 in Triple-Negative Breast Cancer

Abstract: Triple-negative breast cancer (TNBC) is a highly aggressive form of breast cancer. Aberrant expression of genes in mTOR pathway and their targeting miRNAs plays an important role in TNBC. The aim of this study was to determine the expression of mTOR and S6K1 and their targeting miRNAs in breast cancer cell lines and clinical samples. miRNAs targeting 3'-UTR of mTOR and S6K1 mRNAs were predicted using bioinformatic algorithms. MDA-MB-231, MCF-7, and MCF-10A as well as 20 TNBC samples were analyzed for gene and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 54 publications
1
24
0
Order By: Relevance
“…Ju et al found hsa-miR-3182 was up-regulated in lung adenocarcinoma cell lines with EGFR exon 19 deletion (H1650 and PC9) than in wild-type (H1299 and A549) [25]. Razaviyan et al found miR-3182 is up-regulated in breast cancer cell lines MDA-MB-231 than in normal breast cell line MCF-10A and miR-3182 may play a tumour-suppressive role by targeting mTOR and S6K1 Genes of mTOR signalling pathway in triple-negative breast cancer [26]. In this research, we revealed linc00858 was up-regulated especially in lung tissues and in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Ju et al found hsa-miR-3182 was up-regulated in lung adenocarcinoma cell lines with EGFR exon 19 deletion (H1650 and PC9) than in wild-type (H1299 and A549) [25]. Razaviyan et al found miR-3182 is up-regulated in breast cancer cell lines MDA-MB-231 than in normal breast cell line MCF-10A and miR-3182 may play a tumour-suppressive role by targeting mTOR and S6K1 Genes of mTOR signalling pathway in triple-negative breast cancer [26]. In this research, we revealed linc00858 was up-regulated especially in lung tissues and in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, has‐miR‐3182 shows also highly up‐regulation in the same time period by microarray analysis. Recently, miR‐3128 have been reported that may attenuate proliferation, migration, and invasion of tumor cells, and inhibited osteosarcoma cell (Zhu, Ma, & Zhang, 2017), retinoblastoma cells (Wang et al, 2020), and breast cancer cells (Razaviyan et al, 2018) growth in vitro and vivo. The present results demonstrated that miR‐199b‐5p overexpression inhibited the growth of C3H10T1/2 cells (Figure 2c).…”
Section: Discussionmentioning
confidence: 99%
“…miR-3182 was recently discovered to be involved in the regulation of certain human diseases. Razaviyan et al (24) illustrated that the expression level of miR-3182 was declined in triple-negative breast cancer. They discovered that miR-3182 may be an effective inhibitory agent for ribosomal protein S6 kinase B1 and mTOR.…”
Section: Discussionmentioning
confidence: 99%